Avaliação cognitiva da queixa de memória na atenção primária: estudo descritivo e longitudinal - MARCOS LEANDRO PEREIRA (2023)
Memory complaints (MQ) are common in the elderly. It is essential to characterize them from a clinical, cognitive and psychiatric point of view, as well as investigate prognostic factors associated with conversion to dementia. This doctorate consists of two studies. The first (Study 1) aims to investigate the functional outcome of individuals with memory complaints and explore the risk factors associated with cognitive and functional declines. The second study aims to investigate the relationship between QM and symptoms of depression. Data from Study 1 were collected between 2016 and 2020 (average follow-up = 44.5 ± 6.8 months) in primary health care in Patos de Minas. Participants were assessed using cognitive tests, Neuropsychiatric Inventory and Functional Activities Questionnaire. The initial sample (2016) consisted of 91 participants, classified as Subjective Cognitive Decline (DCS n=15), Mild Cognitive Impairment (MCI, n=45) or Dementia (n=31). During follow-up, eight individuals died and 26 were not located. Fifty-seven participants underwent clinical reassessment. Of the 15 individuals with DCS (seven not localized, 46.7%), four (26.7%) progressed to MCI and four (26.7%) remained stable. Of the 45 individuals with MCI (eleven not localized, 24.4%), two (4.4%) died, six (13.4%) progressed to dementia, twelve (26.7%) regressed to DCS and fourteen (31.1%) remained stable. Of the 31 individuals with dementia (eight not localized, 25.8%), six (19.4%) died, two (6.5%) regressed to DCS, seven (22.6%) regressed to MCI, and eight remained stable (25.8%). The clinical improvement was due to the treatment of reversible causes, such as hypothyroidism, hypovitaminosis B12 and mood and anxiety disorders. The Study 2 sample consisted of 246 individuals, 77.2% of whom were women, with an average age of 67.2 years (±9.29) and average education of 7.39 years (±5.17). Participants were separated into two groups: with depression and without depression, according to their GDS (Geriatric Depression Scale) score. There was a statistically significant difference for the variables There was a statistically significant difference between the subgroups (depression vs without depression) in the variables Memory Complaints Questionnaire (MAC-Q, p=0.001), Mini Mental State Examination (MMSE, p=0.006), Delayed Memory of the figure test ( p=0.030), Semantic Verbal Fluency (animals) (p=<0.001), Clock Drawing Test (p=0.018), Montreal Cognitive Assessment (MoCA, p=0.011), Geriatric Anxiety Inventory (GAI, p= <0.001) and Functional Activities Questionnaire (FAQ, p=<0.001), with the worst cognitive performance in individuals with depression. The Study 2 sample consisted of 246 individuals, of which 77.2% were women, with an average age of 67.2 years (±9.29) and average education of 7.39 years (±5.17). Participants were separated into two groups: with depression and without depression, according to their GDS (Geriatric Depression Scale) score. The multinomial regression model revealed that having higher grades on the GDS (OR 0.61; 95% CI 0.49 – 0.75; p <0.001), older ages (OR 0.90; 95% CI 0.84 – 0.97; p=0.007), hypothyroidism (OR 20.15; 95% CI 1-92 – 211.00; p=0.012) and smoking (OR 9.34; 95% CI 2.93 – 2.97; p<0.001) are variables associated with cognitive decline/dementia. Furthermore, it was noticed that depression is associated with the female sex (OR 0.44; 95% CI 0.20-0.94; p= 0.034) and anxiety (OR 37.91; 95% CI 12.31 – 116.76; p<0.001, while cognitive normality was associated with the absence of depression (OR 14.20; 95% CI 4.26 – 47.29, p < 0.001). The results of Study 1 reinforce the need for adequate screening and treatment of reversible causes of cognitive decline in primary care. In Study 2, age and education were variables associated with dementia. Depression was associated with cognitive deficits and functional decline, reinforcing the growing literature on the relevance of depression as an impact factor on the cognitive-functional performance of elderly people.